2016
DOI: 10.1007/s10863-016-9687-3
|View full text |Cite
|
Sign up to set email alerts
|

Simple oxygraphic analysis for the presence of adenylate kinase 1 and 2 in normal and tumor cells

Abstract: The adenylate kinase (AK) isoforms network plays an important role in the intracellular energy transfer processes, the maintenance of energy homeostasis, and it is a major player in AMP metabolic signaling circuits in some highly-differentiated cells. For this purpose, a rapid and sensitive method was developed that enables to estimate directly and semi-quantitatively the distribution between cytosolic AK1 and mitochondrial AK2 localized in the intermembrane space, both in isolated cells and tissue samples (bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…It is upregulated in human CRC [37] with the total AK activity about 2 times higher than surrounding normal tissue [10]. The same was also observed in tumor cells of other histological types [38]. The AK system could play an important role in the adaptation of cancer cells to an unfavorable microenvironment and tumor progression [39,40].…”
Section: Toxicity Of Cpps On Caco-2 Cellsmentioning
confidence: 70%
“…It is upregulated in human CRC [37] with the total AK activity about 2 times higher than surrounding normal tissue [10]. The same was also observed in tumor cells of other histological types [38]. The AK system could play an important role in the adaptation of cancer cells to an unfavorable microenvironment and tumor progression [39,40].…”
Section: Toxicity Of Cpps On Caco-2 Cellsmentioning
confidence: 70%
“…Moreover, PrePhyloPro predicted the high correlations (Jaccard similarity >0.95) between α∕β subunits and adenylate kinase isoforms (AKs) ( Table S7 ). Consistently, AKs maintain the cellular energy balance and collaborate in ATP synthesis, especially through coupling of the mitochondrial resident AK2 with the OXPHOS activity ( Klepinin et al, 2016 ). Additionally, the transcription of AK2 and α∕β subunit are both enhanced by triiodothyronine ( Severino et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics studies have revealed up-regulation of AK2 in human prostate and pancreatic cancer cells [ 75 , 76 ]. It was shown that AK2 can promote cell proliferation under normal circumstances and high expression of AK2 can be associated with poorly differentiated cells with high proliferative index, and that strong differences exist between highly differentiated and tumor cells in the affinity of their mitochondrial respiration for exogenous AMP [ 49 , 77 , 78 ]. The signaling function of AK realizes through the amplifying a small change in the ATP/ADP ratio into a much higher increase in the AMP/ATP ratio that in turn activates several cellular AMP-sensitive components, including those in the glycolytic and glycogenolytic pathways, and metabolic sensors and effectors such as ATP-sensitive potassium channels and AMP-activated protein kinase, which adjust energy state in the given tissue [ 1 , 49 , 79 ].…”
Section: Quantitative Assessment Of Intracellular Diffusion Restrimentioning
confidence: 99%
“…Critical steps: Cells with a low K m(ADP) should be measured at low (0.1 mM) ATP concentrations, while for cells with higher K m(ADP) vales the use of higher (2 mM) ATP concentrations is recommended [ 77 ]. Representative traces can be found in [ 30 , 77 ].…”
Section: Quantitative Assessment Of Intracellular Diffusion Restrimentioning
confidence: 99%